2010
DOI: 10.1172/jci42447
|View full text |Cite
|
Sign up to set email alerts
|

Distinct growth hormone receptor signaling modes regulate skeletal muscle development and insulin sensitivity in mice

Abstract: Skeletal muscle development, nutrient uptake, and nutrient utilization is largely coordinated by growth hormone (GH) and its downstream effectors, in particular, IGF-1. However, it is not clear which effects of GH on skeletal muscle are direct and which are secondary to GH-induced IGF-1 expression. Thus, we generated mice lacking either GH receptor (GHR) or IGF-1 receptor (IGF-1R) specifically in skeletal muscle. Both exhibited impaired skeletal muscle development characterized by reductions in myofiber number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(153 citation statements)
references
References 75 publications
6
138
1
4
Order By: Relevance
“…Skeletal muscle protein synthesis is resistant to the anabolic action of insulin in patients with sarcopenia [9]. Signal of insulin-like growth factor (IGF)-1, which has an important role on skeletal muscle mass [37,38], is decreased in insulin resistance [39]. On the other hand, the relationship between insulin resistance and NAFLD has also been recognized [40].…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle protein synthesis is resistant to the anabolic action of insulin in patients with sarcopenia [9]. Signal of insulin-like growth factor (IGF)-1, which has an important role on skeletal muscle mass [37,38], is decreased in insulin resistance [39]. On the other hand, the relationship between insulin resistance and NAFLD has also been recognized [40].…”
Section: Discussionmentioning
confidence: 99%
“…To study the GH action on muscle, two independent muscle-specific GHRKO mice were generated using different promoters/enhancers. The first used Mef-2c-73k promoter/enhancer to knock out GHR in muscle (304); the second used muscle creatine kinase (MCK) promoter/enhancer (305,306,307). Mef-2c-73k is expressed in adult muscle and fetal heart and brain, while MCK is expressed in skeletal and cardiac muscle during all stages of development.…”
Section: Muscle-specific Ghrkomentioning
confidence: 99%
“…This difference may be used to explain the differences between these two mouse lines. That is, the changes of growth, body compositions and insulin sensitivities were opposite in these two lines (304,305,306,307,308). Importantly, the MCK males increased maximum lifespan along with decreased inflammation (305,307,308) and they were protected from HF diet-induced metabolic deterioration(306).…”
Section: Muscle-specific Ghrkomentioning
confidence: 99%
“…Studies using human myoblasts and myotubes suggest that muscle expresses higher levels of IGF-1 receptor (IGF1R) relative to insulin receptor (IR) (9), but in vivo studies suggest that both may be involved in maintenance of muscle mass. For example, genetic inactivation of IGF1R in muscle has been reported to cause a mild decrease in muscle fiber size, and deletion of IR in muscle has been suggested to promote age-related muscle atrophy (10,11). We recently showed that combined loss of IR and IGF1R in muscle induces a marked decrease in muscle mass (12), indicating that signaling via IR and/or IGF1R is necessary for normal muscle growth.…”
Section: Introductionmentioning
confidence: 99%